Effects of alcohol extract from defatted soybean meal on bile acid level, digestive enzyme activity and nutrient digestibility of pompano (Trachinotus blochii) - Hung, Nguyen Phuc; Thinh, Do Van (Academia Journal of Biology, 2020)
Defatted soybean meal (SBM), which is produced by defatting soybean with solvents, has been considered as the most cost-effective substitute for fish meal (FM) in fish diets. However, SBM contains alcohol-soluble components which may interfere with growth performance and digestive physiology of fish. This study examined the effects of alcohol extract (Ext) containing alcohol-soluble components extracted from SBM on bile acid level, digestive enzyme activity and nutrient digestibility of pompano Trachinotus blochii. SBM was processed and separated into Ext and ethanol-extracted SBM (ESBM), thus, ESBM was SBM without alcohol-soluble components. Four experimental diets were formulated, denoted as FMD (FM-based diet), SBMD (SBM-based diet), ESBMD (ESBM-based diet), and ESBM+ExtD (ESBM-based diet plus Ext). Each diet was fed to two groups of fish (20 fish/group, 25 g/fish) for 4 weeks. Results showed that plasma lipid components, anterior intestinal bile acid level, anterior intestinal trypsin and lipase activities, and protein and lipid apparent digestibility coefficients (ADCs) of SBMD -fed fish were similar to those of ESBM+ExtD-fed fish. These parameters were significantly lower in SBMD-fed and ESBM+ExtD-fed fish than in ESBMD-fed and FMD-fed fish (P < 0.05). There were no significant differences in plasma total cholesterol level, trypsin activity, and protein ADC between ESBMD and FMD groups, however, total bile acid level, lipase activity, and lipid ADC were significantly lower in ESBMD -fed fish than fish fed FMD (P < 0.05). These results indicated that alcohol extract containing alcohol-soluble components extracted from SBM inhibited the secretions of bile acids and pancreatic digestive enzymes in pompano fish, and these abnormalities might impair nutrient digestion and absorption. The findings of the present study suggested that removing alcohol extract and supplementation of taurine could be effective for improving nutritional quality of SBM and enhancing feed utilization and growth performance of pompano which were fed SBM-based diets.